PENERAPAN STRATEGI PEMBELAJARAN LABORATORY TRAINING UNTUK MENINGKATAN HASIL BELAJAR IPA SISWA KELAS IV SDN 001 AIRTIRIS KABUPATEN KAMPAR - Sonto Siswoyo; Syahrilfuddin Syahrilfuddin; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to improve learning outcomes IPA fourth grade students of SDN 001 Airtiris Kampar regency. This research was conducted in the fourth grade SDN 001 Airtiris Kampar, while the time the study was conducted in the academic year 2015/2016. Design of this research is the Classroom Action Research (PTK). The implementation of cooperative learning model Laboratory Training to improve student learning outcomes fourth grade SDN 001 Airtiris Kampar commencing on 18 April until 28 April 2016 and implemented in accordance with the timetable in the fourth grade SDN 001 Airtiris Kampar regency. Berdasarkn results, it can be concluded that the cooperative learning model Laboratory Training can improve learning outcomes IPA fourth grade students of SDN 001 Airtiris Kampar regency. Average price of a base score of 59.31 increased in the first cycle with the average being 66.55 compared with a base score, which means the increase is 12:20%. In the second cycle occurs on average 78.62% increase in 18:13. The quality of teaching and learning processes in teacher activity after implementation of cooperative learning model Laboratory Training increased from the first cycle of the first meeting by 63% in the second meeting increased to 96%. While the student activity also increased after the implementation of cooperative learning model Laboratory Training in the first cycle have gained 1 percentage meetings by 63% and by 71% 2 meeting.Key Words: Results to Learn Science, Laboratory Training